2014
DOI: 10.1007/s11547-014-0397-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of “Time-Out” checklist in interventional radiology procedures as a tool to enhance patient safety

Abstract: The use of a checklist in IR, named "Time-Out" in our experience was feasible and effective allowing elimination of adverse events in the first year of use and promoting significant involvement and awareness of patient safety among the health-care team. The level of implementation, completeness and acceptability of the SC within the team increased after adequate training had been provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…These findings align with other interventional radiology studies . A study conducted in a radiology department in Italy found that the patient name and site were the most commonly completed items in a baseline audit, while the time, barcode and biological samples were the most frequently ignored items …”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…These findings align with other interventional radiology studies . A study conducted in a radiology department in Italy found that the patient name and site were the most commonly completed items in a baseline audit, while the time, barcode and biological samples were the most frequently ignored items …”
Section: Discussionsupporting
confidence: 86%
“…9,10 A study conducted in a radiology department in Italy found that the patient name and site were the most commonly completed items in a baseline audit, while the time, barcode and biological samples were the most frequently ignored items. 12 There was a marked discrepancy between the percentage of the checklist completed (64% compliance) in the medical record and what was documented during the observations (38%). This was also the case for our study into surgical SCs (86% in the records and 27% observed).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations